PELATIHAN SEHARI BAHASA INGGRIS PARIWISATA DAN PENYUSUNAN RENCANA PERJALANAN OLEH PEMANDU WISATA LOKAL, KELOMPOK SADAR WISATA, DI DESA WISATA TISTA KABUPATEN TABANAN, BALI - I Putu Andri Permana; I.A Putri Gita Ardiantari; Putu Regina Yohana Pratiwi (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
Tista Village is a village with qualified tourism potential to be developed further. There are many places to visit and activities to experience in this village while exploring the existing culture and local wisdom. However, the biggest obstacle faced by this village is the management or governance ability of their tourism potential, such as a lack of English Skills and understanding of tourist travel plans in bringing tourists to existing places and doing the activities they want, etc. Providing quality knowledge and information to visitors requires the expertise of a tour guide armed with a neat travel plan, who will later deliver and explain every place and activity carried out in this village. This deficiency is one of the reasons we conduct training on the preparation of travel plans or often called an itinerary so that visitors' trips to enjoy the beauty of this village remain organized and well-planned. We conducted this training with presentation and practice methods when they immediately arranged in a table starting from the places to visit and the duration of time required in each location and activity before being presented to other participants. Keywords: Itinerary1, Tour Guides 2, Tourism Village3